Essays from the edge : parerga & paralipomena - Jay, Martin, 1944- (University of Virginia Press, 2011)
Annotation Over his distinguished career as a European intellectual historian and cultural critic, Martin Jay has explored a variety of major themes: the Frankfurt School, the exile of German intellectuals in America during the Nazi era, Western Marxism, the denigration of vision in twentieth-century French thought, the discourse of experience in modern Europe and America, and lying in politics. Essays from the Edge assembles Jay's writings from the intersections of this intellectual journey. Several essays focus on methodological debates in the humanities and social sciences: the limits of interdisciplinarity, the issue of national or universal philosophy, cultural relativism and visuality, and the implications of periodization in historical narrative. Others examine the concept of "scopic regime" and the metaphors of revolution and the gardening impulse. Among the theorists treated at length are Theodor Adorno, Hannah Arendt, Jacques Derrida, and Michel Foucault. The essays also include several of Jay's Salmagundi columns, dealing with subjects as varied as the new Museum of Modern Art in New York, the impact of Colin Wilson's The Outsider, and the demise of the Partisan Review. All of these efforts can be considered what Arthur Schopenhauer called, to borrow the title of one of his most celebrated collections, "parerga and paralipomena." As essays from the edges of major projects, they illuminate Jay's major arguments, elaborate points made only in passing in the larger texts, and explore ideas farther than would have been possible, given the focus of the larger works themselves. The result is a lively, diverse offering from an extraordinary intellect
Keywords: Philosophy, Modern -- 21st century.; History -- Philosophy.; Humanities -- Philosophy.; Intellectual life -- 21st century.; Civilization, Modern -- 21st century.; Philosophie -- 21e siècle.; Vie intellectuelle -- 21e siècle.; Civilisation -- 21e siècle.; Histoire -- Philosophie.; LITERARY COLLECTIONS -- American -- General.; HISTORY -- World.; Civilization, Modern; History -- Philosophy; Humanities -- Philosophy; Intellectual life; Philosophy, Modern; 2000-2099